The Feasibility Of Diversification Strategies On The Transformation Of Coal Mining Companies Into Mineral Mining Companies In Indonesia - Aulia Pradipta Luthani (Jurnal Pendidikan Indonesia, 2025)
Following the global commitment on net zero emissions during the Paris Agreement in 2016, Indonesia is fulfilling its commitment by focusing their strategy on electric vehicles batteries investment and decreasing the coal-based power generation. One of the company groups in Indonesia that mainly operating on coal starts to look at green minerals that would increase in demand as a diversification strategy. This study aims to investigate which green mineral options that would be the most feasible strategy for the company through decision-making method. Based on the literature review on business strategy and decision-making method decision tree analysis, a questionnaire was distributed across the internal team of the target company that works on the diversification attempt. The respondents were asked on their confidence on the proposed green mineral options. Analysis on the responses shows that there is a strong, if not perfect, relationship between the confidence scores and all the calculated expected monetary values (EMV) of the proposed green minerals. The analysis also shows that the highest EMV compared to other green mineral option, is gold. On this basis, it is recommended for the company to choose gold as their diversification strategy on green minerals. Further research is needed to investigate other factors that has not been covered in this dissertation, or to investigate through other decision-making method.